PENGARUH FAKTOR MAKROEKONOMI TERHADAP TINGKAT KREDIT BANK SERTA IMPLIKASINYA PADA KESEHATAN PERBANKAN - Purba, Agnes Sheryta Anastasya; Sakti, Rachmad Kresna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to determine the effect of Interest Rates, Rupiah Exchange Rates, and Total Exports on Bank Credit Levels and their Implications on Banking Health from 2013 - 2020, where the crucial role of credit in the banking world is in the midst of fluctuating macroeconomic factors as the basis for problems that exist at the time. research is done. This study uses the Simultaneous Method to analyze whether there is an influence of Macroeconomic Factors as the dependent variable on the Credit Level and Banking Health as independent variables. From this research, it is known that market power at interest rates, rupiah exchange rates, and low exports can increase bank credit levels, while the market power of large banks is higher than that of small banks. The results also show that large banks have higher levels of bank credit. This result also supports the health of banks, the higher the level of bank credit, the health of the bank will be more stable or even better.